2008
DOI: 10.1124/jpet.108.145037
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Mitochondrial Oxidative Stress in Sulfur Mustard Analog 2-Chloroethyl Ethyl Sulfide-Induced Lung Cell Injury and Antioxidant Protection

Abstract: Sulfur mustards (SMs) have been used as warfare agents since World War I and still pose a significant threat against civilian and military personnel. SM exposure can cause significant blistering of the skin, respiratory injury, and fibrosis. No antidote currently exists for SM exposure, but recent studies, using the SM analog 2-chloroethyl ethyl sulfide (CEES), have focused on the ability of antioxidants to prevent toxicity. Although antioxidants can prevent CEES-induced toxicity, the mechanisms by which these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
86
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 39 publications
10
86
0
Order By: Relevance
“…Although AEOL 10150 did not appear to improve GSH levels, this effect may be complicated by the formation of SM-GSH adducts which would not have been detected by the HPLC methods used here (Batal et al, 2015;Mol et al, 2008). Other publications investigating oxidative stress and vesicants have concluded that reductions in the measured markers of oxidative stress are linked to lowered toxicity (Gould et al, 2009;Laskin et al, 2010;O'Neill et al, 2010;Tewari-Singh et al, 2011;Ucar et al, 2007). Our results support the hypothesis that AEOL 10150 lowered oxidative stress in this model, which correlated with attenuating SM toxicity.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Although AEOL 10150 did not appear to improve GSH levels, this effect may be complicated by the formation of SM-GSH adducts which would not have been detected by the HPLC methods used here (Batal et al, 2015;Mol et al, 2008). Other publications investigating oxidative stress and vesicants have concluded that reductions in the measured markers of oxidative stress are linked to lowered toxicity (Gould et al, 2009;Laskin et al, 2010;O'Neill et al, 2010;Tewari-Singh et al, 2011;Ucar et al, 2007). Our results support the hypothesis that AEOL 10150 lowered oxidative stress in this model, which correlated with attenuating SM toxicity.…”
Section: Discussionsupporting
confidence: 80%
“…Catalytic antioxidants can scavenge multiple reactive oxygen and nitrogen species without being consumed in the reaction (Day, 2004). This antioxidant has shown promising effects in other studies of SM induced toxicity in both in vitro and in vivo models (Gould et al, 2009;O'Neill et al, 2010O'Neill et al, , 2011Tewari-Singh et al, 2014). This catalytic antioxidant has also displayed therapeutic benefits in other models of lung injury such as exposure to fractionated radiation and chlorine gas inhalation (McGovern et al, 2011;Rabbani et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from HD, its monofunctional analog 2-chloroethyl ethyl sulfide (CEES) also causes several skin toxic effects comparable with HD, and therefore CEES is used extensively to uncover the mechanism of action of HD and to screen effective therapeutic agents (Han et al, 2004;Paromov et al, 2007;Gould et al, 2009;Tewari-Singh et al, 2009. HD/CEES-caused oxidative stress results in the 8-oxo-2-deoxyguanosine DNA adduct as well as lipid and protein oxidation, which can cause inflammation and other toxic responses in skin Black et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The standard mouse ear animal model for studying pathophysiology of SM-induced skin lesions have been shown to have altered reaction to injury with delayed inflammatory changes compared to mouse skin 78 . Animal models exposed with 2-chloroethyl ethyl sulphide [CEES; half mustard, used to produce SM like skin lesions] provides the initial steps for evaluation of therapies that need to be repeated using SM due to differences in the metabolism and the mechanism of action 105,106 . Thus, use of CEES as a stimulant of SM for antidote evaluation may not be appropriate.…”
Section: Models Systems For Screening Sm Toxicitymentioning
confidence: 99%